Three dimensional changes in maxillary complete dentures immersed in water for seven days after polymerization - Shinsuke Sadamori; Toshiya Ishii; Taizo Hamada; Arifzan Razak (Dental Journal (Majalah Kedokteran Gigi), 2008)
The purpose of this study was to investigate the three dimensional changes in the fitting surface and artificial teeth of maxillary complete dentures which were fabricated using two different polymerizing processes: heat polymerization (HP) and microwave polymerization (MP), after immersion in water for seven days. The amount of distortion in the molar region of the alveolar ridge was significantly different between HP and MP. However, the overall distortion of the dentures polymerized using both methods was similar. The distortion due to immersion in water for seven days compensated for the polymerization distortion, but the amount of distortion was very slight.